An Inventory Model with Embeeded Acceptance Sampling Plan - Konda Reddy, N; Murali Krishna, K; V.N. Murty, A (International Journal of Engineering and Technology, 2018)
The classical inventory model assumes that the quality of the items received matches with the quality required. In many cases the deviation in quality results in additional costs to the stockiest and sometimes lead to rejection of the received lot. The cost of inspection along with the other inventory costs can be unified into a single model by embedding an acceptance sampling plan into the inventory model. When the lot is accepted there is a possibility of unseen defectives, which may reach the customer leading to loss of goodwill. If the lot is rejected on inspection, the model suggests rectification and removal of non-confirming units. In this paper a model is developed to determine (i) the Economic Order Quantity and (ii) a single sample plan of the attribute type, which minimizes the Average Total Inspection. The model utilizes spreadsheet solutions to handle statistical functions.Â Â